First record of the wolf spider subfamily Artoriinae and the genus Artoria from China (Araneae: Lycosidae) - Li, Zongxu; Framenau, Volker W.; Zhang, Zhi-Sheng (Zootaxa, 2012)
The subfamily Artoriinae Framenau, 2007 is here firstly recorded from China, by reporting Artoria parvula Thorell, 1877and Artoria ligulacea (Qu, Peng & Yin, 2009) comb. nov. from Yunnan Province. These records, the first of the genusnorth of the Tropic of Cancer, represent a considerable range extension of the subfamily, which is considered of Gondwanan origin.